A Brief Note On Time Evolution of Quantum Wave Function and of Quantum Probabilities During Perception and Cognition of Human Subjects - Conte, Elio (NeuroQuantology, 2009)
We apply our theory of quantum time dynamics of cognitive entities to experimental data in order to calculate the time evolution of quantum wave function and of quantum probabilities during cognitive processes of the human subject. The results are used in order to elucidate the mind mechanism of human decision under the perspective of quantum mechanics.